MORPHOLOGICAL AND MOLECULAR BIOLOGICAL DETERMINANTS OF REPEATED IMPLANTATION FAILURE - Orazov Mekan; Lokshin Vyacheslav; Silantyeva Elena; Mikhaleva Liudmila; Kamillova Dilorom; Orekhov Roman; Melekhina Irina (Scientific Journal of Pedagogy and Economics, 2020)
The evolution of assisted reproductive technology (ART) from classical in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) to the era of predictive models using artificial intelligence has led to a worldwide reproductive revolution in recent years. But despite the significant development of ART, there is still a high prevalence of failed IVF attempts. Thus, although ART improves overall outcomes for infertile couples, some problems still remain unresolved, such as repeated implantation failure (RIF). The term RIF is applicable only in IVF programs. RIF is a complex and urgent problem of modern reproductology. It has a wide range of understudied etiological factors and pathogenesis mechanisms. The pathogenesis of implantation failures is based on a variety of polygenic and polymorphic mechanisms of defective receptivity due to disturbance of endometrial architectonics. Management of RIF should be individualized taking into account its pathogenesis patterns using methods based on the principles of evidence-based medicine. Randomized clinical trials with large statistical samples and with a thorough consideration of clinical and morphological patterns are necessary to understand the mechanisms of its realization further and to overcome the problem.